QoS aware MAC with admission control for supporting VOIP over wireless ad hoc networks - Mohandas Pai Achuth. (2008)
This project will be proposing a new scheme that extends EDCF, by the inclusion of Admission Control mechanisms for the voice traffic over ad hoc networks and adoptively adjusting the contention window for the data traffic based on the network conditions. Based on the proposal, extensive simulations were done in order to prove its suitability and performance guarantee for supporting voice applications on ad hoc networks.